Sex differences in the association between peripheral inflammation and melancholia symptoms - Christopher F. Sharpley; Vicki Bitsika; Wayne M. Arnold; Ian D. Evans; Emmanuel Jesulola; Linda L. Agnew (Psychiatry Research Communications, 2024)
Melancholia represents a particular subtype of depressive symptomatology. Unlike Major Depressive Disorder (MDD), Melancholia has not been conclusively associated with peripheral inflammation, although there may be some methodological reasons confounding that finding. To overcome some of those methodological limitations, the correlation between one index of peripheral inflammation (C-Reactive Protein: CRP) and Melancholia was investigated in a community sample of 40 male and 51 female participants (aged 18–75 years) who provided a blood sample and self-report data on an established measure of Melancholia (MEL). Results indicated that females had significantly higher concentrations of CRP than males, and that there were different patterns of association between the MEL items and CRP for males and females. Although the predominant differences were for the MEL symptoms of cognitive confusion (females only) and feelings of low self-worth (males only), each sex had distinct networks of associations between CRP and the eight MEL items used here. These findings may provide some explanation of the lack of clear results regarding the CRP-Melancholia link in the previous literature, and also argue for development of clinical assessment and treatment approaches that differ for males and females.